(untitled) (Research, Society and Development, 2021)
The essay proposes to reflect on the importance of decent home for quilombola communities, taking into account the ancestors that make up their memories, histories, cultures, habits, customs and actions as a fundamental dimension of their identities. To this end, the symbolism of the house and its role in the specific construction of the individuals who inhabit it are part of this heritage and its essences. Intersecting with a heritage theme, the traditional architecture of the quilombolas in Volta do Campo Grande, a community located in the city of Campinas do Piauí, is chosen as an empirical object. The following question is presented as a research problem: What are the material and immaterial elements involved in the process of identifying quilombolas in Volta do Campo Grande with their homes? It comprises methodological procedures, bibliographic and documentary studies, direct observation, identification and photography. For some quilombolas in the studied community, a stone, among other functions - resource and aesthetic -, plays the role of symbolic covering of memory. In this way, the home that can be considered the space of the soul is also the means by which they can be recognized.